CHILDREN’S FASHION AND IDENTITY - Sulasih Nurhayati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2011)
This article attempts at exploring the identity formation through children’s fashion, in particular adjusted to famous characters on cartoon movies. By ‘children’ means that they are also subjects to whose identity fashion presumably contributes to shape, which is continuous and has the future. By using some theories about fashion and identity from traditional, modern, and postmodern, supported by the awareness of media’s role on constituting consumerism culture amongst children, the fashion’s role in constructing children’s identity is in details scrutinized. As a result, children’s identity formation through fashion is mostly due to their liking on certain characters on cartoon movies. This liking is influenced by media’s role on constituting their consumerism towards the movie and fashion adoration. However, the influence of media power can not represent completely the ‘truer’ identity since it has history as well as future, which will always revolve in such a never-ending cycle. If it is not a direct contribution, it aids to support the ‘idealized’ identity construction, which is worthily appropriate to postmodern societies.